Effect of curcumin and Garcinia kola on the cerebellum of the transected sciatic nerve of the diabetic rats: glial and neuronal evidence - Marangoz, Abdullah Hilmi; Hamour, Hala Mahgoub; Kaplan, Arife Ahsen; Alkan, Işınsu; Altun, Gamze; Kaplan, Süleyman (Frontiers in Neuroscience, 2026)
ObjectivePeripheral nerve injury and diabetes can lead to some serious neurodegenerative changes in central nervous system structures. Curcumin and Garcinia kola are considered natural compounds with known antioxidant and neuroprotective properties. The current study aims to investigate the effects of curcumin and Garcinia kola on granular cells, glial cells, and Purkinje cells in a diabetic rat model induced by sciatic nerve transection, using stereological and immunohistochemical approaches.MethodThirty-five male adult rats were divided into five groups: Control, Sham (Transected Sciatic Nerve), Transected Sciatic Nerve + Diabetes (T + DM), T + DM + Curcumin (T + DM + Cur), and T + DM + Garcinia kola (T + DM + GK). Ninety days after the sciatic nerve injury, the rats' cerebellar tissues were dissected and processed into paraffin and resin blocks. Volumetric fractions of cortical layers and white matter were estimated using the Cavalieri principle. Apoptosis and glial activation were assessed by immunohistochemical analysis.ResultsStereological analyses revealed that the volume fraction of the molecular layer was significantly lower in the T + DM + Cur group compared to the T + DM + GK and T + DM groups. A significant decrease in the volume fraction of the Purkinje cell layers was observed in the T + DM + Cur group compared to the Sham group. No significant differences were found between the groups in the granular layer and white matter volume fractions. Immunohistochemical analysis revealed inhibition of caspase-3 activity in the T + DM group. However, intense caspase-3 activation was also observed in the Control and T + DM + Cur groups.ConclusionSciatic nerve transection, combined with diabetes, leads to significant structural and cellular changes in the cerebellar cortex. The mechanisms underlying the anti-apoptotic effects of diabetes on granular cells and other cerebellar components should be investigated in detail.